The Superiority of Willpower over Firepower: A Philosophical Analysis of Vietnamese Resistance against the United States, 1954–1975 - Riyanto Wujarso; Muhammad Arif Saifudin; Joni Widjayanto (Jurnal Ilmiah Global Education, 2026)
The Vietnam War (1954–1975) stands as a crucial case study of asymmetric conflict, where a major military superpower (the US) was defeated by an ideologically grounded resistance movement. This research specifically argues that Vietnam’s victory was a classic case of the superiority of willpower over firepower. The study’s primary objective is to analyze the essence and implementation of the "People’s War" doctrine as the ideological foundation of the resistance. The methodology employed is a qualitative historical case study utilizing content analysis of key military doctrine documents, historical monographs, and academic journals. Key findings indicate that the People’s War philosophy consistently positioned political struggle (Dau Tranh Chinh Tri) as the strategic determinant of armed struggle, creating a framework of total resistance that fully integrated the civilian populace. The operational implementation of this philosophy, especially through the Cu Chi Tunnels and the psychological strategy of the 1968 Tet offensive, effectively neutralized the overwhelming American firepower. The Tet offensive serves as a causal proof, where tactical losses were exchanged for a devastating political-psychological victory that broke the US’s will to continue the war (willpower). This study concludes that the Vietnam War was "More Than Just a Battle." Vietnam’s success was generated by a defense philosophy that successfully mobilized limitless moral power a decisive strategic advantage that western military metrics failed to measure or destroy.